Analisis Perbandingan Likuiditas Terhadap Profitabilitas - Sri Nuringwahyu; Trianti, Khoiriyah; Sholikhah, Lutfiatus (Institut Teknologi dan Sains Mandala, 2024)
This study aims to examine the causal relationship between the liquidity ratio as measured using the cash ratio and loans deposit ratio to bank profitability as measured using Return On Assets (ROA). This test was carried out on two banks, namely conventional commercial banks and Islamic commercial banks in Indonesia. The population used in this study are all Conventional Commercial Banks and Islamic Commercial Banks listed on the Indonesia Stock Exchange. The data used is secondary data. Secondary data is obtained from the financial statements published by the bank during the observation period. The observation period used is 2019-2022. Data at Conventional Banks is not normally distributed, so a relationship analysis is carried out, the relationship between the Cash Ratio and the Loans-Deposit Ratio shows that it is in a moderate position. Relationship Cash Ratio to Return On Assets, shows in a low position Relationship of Loans Deposit Ratio to Return On Assets, shows in a low position at Islamic Banks with correlation results: Relationship Cash Ratio to LoansDeposit Ratio shows in a moderate position. Relationship Cash Ratio to Return On Assets, shows in a strong position. The relationship between Loans Deposit Ratio and Return On Assets is in a moderate position. In Islamic Banks, regression analysis can be carried out because the data is normally distributed, the results of the regression analysis are Cash Ratio which has a significant effect on ROA while LDR does not have a significant effect on ROA. Simultaneously Cash ratio and LDR have a significant effect on ROA. Keywords: Cash ratio, Loan deposit ratio, ROA, Conventional Commercial Banks, Islamic Commercial Banks, not normally distributed, correlation, regression